2003
DOI: 10.1046/j.1365-2141.2003.04216.x
|View full text |Cite
|
Sign up to set email alerts
|

Over‐expression of short isoforms of Helios in patients with adult T‐cell leukaemia/lymphoma

Abstract: Summary.In previous studies, we demonstrated an overexpression of the dominant-negative isoform of the transcription factor Ikaros in patients with blast crisis of both chronic myelogenous leukaemia and B-cell acute lymphoblastic leukaemia (ALL). Recently, we reported an overexpression of the short isoforms of Helios, which is one of the members of the Ikaros gene family, in a patient with T-cell ALL. In the present study, we found over-expression of short isoforms of Helios in human T lymphotropic virus-I (HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…IKZF2 encodes Helios, a T cell-restricted Ikaros-family transcription factor, and is expressed in various PTCLs. [42][43][44][45] IKZF2 was expressed similarly in TCL75 and other cases, whereas ERBB4 was expressed only in TCL75 exons 2 to 28 encoded by IKZF2-ERBB4, which includes the ERBB4 kinase domain (supplemental Figure D-E). Thus, the fusion, which contains only exons 1 to 2 of IKZF2, co-opts the IKZF2 promoter for expression.…”
Section: Mpseq/rnaseq Identifies Novel Kinase Fusions In Ptcl Nosmentioning
confidence: 99%
“…IKZF2 encodes Helios, a T cell-restricted Ikaros-family transcription factor, and is expressed in various PTCLs. [42][43][44][45] IKZF2 was expressed similarly in TCL75 and other cases, whereas ERBB4 was expressed only in TCL75 exons 2 to 28 encoded by IKZF2-ERBB4, which includes the ERBB4 kinase domain (supplemental Figure D-E). Thus, the fusion, which contains only exons 1 to 2 of IKZF2, co-opts the IKZF2 promoter for expression.…”
Section: Mpseq/rnaseq Identifies Novel Kinase Fusions In Ptcl Nosmentioning
confidence: 99%
“…[19][20][21][22][23] Expression of non-DNA-binding isoforms of Helios have been noted in adult cases of T-cell ALL. [24][25][26] To date, a loss-of-function mutation in the Helios gene has not been described so it remains unclear as to whether Helios is also functioning as a tumor suppressor in lymphocytes in a manner analogous to Ikaros and Aiolos.In addition to the function of Ikaros family members in the regulation of lymphoproliferation, Ikaros has also been shown to regulate early developmental decisions within the hematolymphoid system. Mice homozygous for the Ikaros DN mutation died soon For personal use only.…”
mentioning
confidence: 99%
“…The presence of the alternative splice Helios variants was first revealed in research studies utilizing the primary leukemic cells from patients with newly diagnosed ALL (12)(13)(14). In this study, we observed that dominant-negative Helios-Δ326-1431 potentially induces the expression of several oncogenes.…”
Section: Discussionmentioning
confidence: 58%
“…In contrast, the T-cell malignancies were only observed in the gene-targeted mice of Ikaros (30). The related gene Helios has been shown to frequently exhibit multiple dominant-negative isoforms in patients with T-cell acute leukemia (6,(11)(12)(13)(14). In the mouse model, the overexpression of the artificial dominant-negative Helios isoform leads to increased T-cell proliferation, as well as the development of T-cell lymphomas (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation